Penguatan Kompetensi Siswa SMK Jurusan Otomotif di Bandar Lampung - Saputra, Rizal Adi; Kurniawan, Dondi; Sabiqunassabiqun; Nazarrudin, Rizal (FT Universitas Lampung, 2024)
With the rapid advancement of automotive technology, there is a need to improve both educational quality and practical skills to enable students to compete in the workforce. The community service activities were carried out through hands-on training that prioritizes mastery of competencies in the automotive field, from understanding basic theories to practical work in solving problems and using work tools. Emphasis was placed on strengthening problem-solving skills in addressing motorcycle damage, a key component in the Automotive Vocational curriculum. The issues presented were case studies based on real motorcycle problems, where students were given time to resolve them (Problem Solving). The students' understanding was assessed through competency tests aligned with the standards and regulations related to motorcycle damage. The results of this service showed that many students successfully solved the problems presented, but they still faced challenges in applying the Standard Operating Procedures (SOP) that adhered to the provided regulations